If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8w + -6)(8w + 6) = 4w(16w + -24) Reorder the terms: (-6 + 8w)(8w + 6) = 4w(16w + -24) Reorder the terms: (-6 + 8w)(6 + 8w) = 4w(16w + -24) Multiply (-6 + 8w) * (6 + 8w) (-6(6 + 8w) + 8w * (6 + 8w)) = 4w(16w + -24) ((6 * -6 + 8w * -6) + 8w * (6 + 8w)) = 4w(16w + -24) ((-36 + -48w) + 8w * (6 + 8w)) = 4w(16w + -24) (-36 + -48w + (6 * 8w + 8w * 8w)) = 4w(16w + -24) (-36 + -48w + (48w + 64w2)) = 4w(16w + -24) Combine like terms: -48w + 48w = 0 (-36 + 0 + 64w2) = 4w(16w + -24) (-36 + 64w2) = 4w(16w + -24) Reorder the terms: -36 + 64w2 = 4w(-24 + 16w) -36 + 64w2 = (-24 * 4w + 16w * 4w) -36 + 64w2 = (-96w + 64w2) Add '-64w2' to each side of the equation. -36 + 64w2 + -64w2 = -96w + 64w2 + -64w2 Combine like terms: 64w2 + -64w2 = 0 -36 + 0 = -96w + 64w2 + -64w2 -36 = -96w + 64w2 + -64w2 Combine like terms: 64w2 + -64w2 = 0 -36 = -96w + 0 -36 = -96w Solving -36 = -96w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '96w' to each side of the equation. -36 + 96w = -96w + 96w Combine like terms: -96w + 96w = 0 -36 + 96w = 0 Add '36' to each side of the equation. -36 + 36 + 96w = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 96w = 0 + 36 96w = 0 + 36 Combine like terms: 0 + 36 = 36 96w = 36 Divide each side by '96'. w = 0.375 Simplifying w = 0.375
| Y/6=-4 | | 9n+-5+-6= | | 3y=7+2x | | 6+9m-5m=2m+29 | | -1-49= | | -x=-2x+1 | | 3d^3-121=0 | | 118(6x+10)=115 | | -1-(7)2= | | -9x^4+54x^3+45x^2=0 | | 32x3/y4= | | 2x=2x-20 | | 32X3/y4 | | 119-13=-20t | | (2x-8)+41+48=180 | | y=cos(0.04x) | | f(6)=9(6)-10 | | 12+6m=25 | | 2x+4x=74 | | 6x=2(9x+48) | | f(x)=9x-10 | | x^2+3x=340 | | 2a+36=3a+48 | | (-1+(6-3*(-3)))*5= | | 20=2(3x+1)+4x | | 19-3w=14+2x | | 4x-4y+z=4 | | 115/4= | | -19x+6=9 | | (-1+(6-3x(-3)))*5= | | 7s+3=15-5s | | x+17+8=-25 |